2001
DOI: 10.1111/1467-9566.00276
|View full text |Cite
|
Sign up to set email alerts
|

‘Oh, those therapists will become your best friends’: maternal satisfaction with clinics providing physical, occupational and speech therapy services to children with disabilities

Abstract: Little is known about maternal satisfaction with clinics that provide physical, occupational and speech therapy services to chronically impaired children. Because of the frequency and duration of contact between mothers and therapy clinics, this represents a significant gap in the literature on satisfaction with health care providers. This study uses a modified labelling approach to the issue of interactions between the own, the wise and the others as a framework for understanding such satisfaction. Data are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 21 publications
1
16
1
Order By: Relevance
“…Being a part of this network is a distinguishing feature in the lives of parents with people with IDs. Green (2001) has described such networks in Goffmanesque terms, describing them as ‘the wise’ for their sympathetic understanding of parents' lives. Although also a problematic one (Todd & Jones 2003), most parents reported that they wanted ongoing contact with this network in the time after the death of their child.…”
Section: Resultsmentioning
confidence: 99%
“…Being a part of this network is a distinguishing feature in the lives of parents with people with IDs. Green (2001) has described such networks in Goffmanesque terms, describing them as ‘the wise’ for their sympathetic understanding of parents' lives. Although also a problematic one (Todd & Jones 2003), most parents reported that they wanted ongoing contact with this network in the time after the death of their child.…”
Section: Resultsmentioning
confidence: 99%
“…One qualitative study has identified therapists who work with a child with a disability as a main source of support to the mother of the child. Green (2001), a mother of a child with cerebral palsy and a sociologist, interviewed 81 mothers of children with disabilities and found that therapists were a valued source of support because they had frequent and long‐term contact with mothers and ‘they were able to see their children as children, and treat them “just like any other kid” ’ (p. 811). Occupational therapists who form good relationships with mothers may be in a unique position to both offer psychological support and identify vulnerable mothers who may benefit from other professional services, such as a mental health practitioner/psychologist/psychiatrist.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the negative ramifications of both felt and enacted stigma, the literature clearly indicates the resilience and adaptive abilities of carers (e.g. Landsman , Green , Broady ). Carers of children with a disability have reported developing advocacy skills and competence in mediating their children's interactions with wider social environments, and also emphasise the positive and enriching experiences of caring for a loved one (Ryan , Blum , Ryan & Runswick‐Cole , Broady , Carers NSW ).…”
Section: Introductionmentioning
confidence: 99%